2022
DOI: 10.1088/1742-6596/2394/1/012014
|View full text |Cite
|
Sign up to set email alerts
|

Feature Extraction and Naïve Bayes Algorithm for Defect Classification of Manalagi Apples

Abstract: Apple is one of the trees that is widely cultivated and grows in subtropical areas. In Indonesia, there are many areas that cultivate apples, including Malang, Batu, Nongkojajar. One way to increase the economic value of apple farmers is by sorting them before sending them to the market. This is important to do in order to make it easier to determine the quality and selling price of manalagi apples. Most apple sellers will sort the apples manually which results in high costs, difficulty, and inconsistency in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…Alruwaili et al [17] used fast R-CNN to study tomatoes, and the final results showed that the accuracy of the RTF-RCNN proposed in the study was as high as 97.42%, which is better than traditional methods. The most common research direction is using different methods to identify different crops and ultimately obtain relatively suitable methods for identifying various crops [18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…Alruwaili et al [17] used fast R-CNN to study tomatoes, and the final results showed that the accuracy of the RTF-RCNN proposed in the study was as high as 97.42%, which is better than traditional methods. The most common research direction is using different methods to identify different crops and ultimately obtain relatively suitable methods for identifying various crops [18][19][20].…”
Section: Introductionmentioning
confidence: 99%